Relationship of financial literacy to stock market participation - Lakoni, Idham; Nurazi, Ridwan; Aziza, Nurna; Novitasari, Novitasari (Privietlab, 2023)
The research objective aimed to understand and analyze stock market participation among the millennial population in Indonesia. Specifically, this study tested stock market participation against the financial literacy variable. It employed a causality research type with a quantitative analysis approach using path analysis method. The sampling technique was purposive sampling, targeting the millennial and Generation Z populations. The model used was Structural Equation Modeling (SEM) Partial Least Square (PLS) through the Smart PLS software. The research variables included Financial Literacy (LF) with indicators (basic financial knowledge, saving and borrowing, protection, investment) and Stock Market Participation (SMP) with indicators (intention to invest in the stock market, motivational, income, reference to social interaction). The results showed that Financial Literacy significantly affects stock market participation. The final recommendation of this study related to investments in the capital market, especially stocks, is that relevant institutions, particularly the Indonesia Stock Exchange and organizations within it, together with the Financial Services Authority, should continue to provide well-organized education to improve investment understanding among millennials and Generation Z, considering the significant potential of these two generations as technology advances rapidly.